Effectiveness of multimedia tools in enhancing consonant-vowel-consonant reading performance and phonics interest and enthusiasm among kindergarten ESL students - Rhazhiel Dominica P. Pesebre; Rosario F. Quicho; Leila M. Collantes; Carlos N. Lamson Jr.; Jupeth T. Pentang (International Journal of Educational Management and Development Studies)
In the ever-evolving landscape of education, the debate between traditional and modern instructional methods remains a focal point of discussion. The more technology is integrated into classrooms, the more it becomes imperative to scrutinize its effectiveness, especially in the foundational years of learning. Studying the association between multimedia tools and the consonant-vowel-consonant (CVC) reading performance of preschool English as Secondary Language (ESL) students is vital. The study explored the effectiveness of multimedia tools on CVC reading performance and interest and enthusiasm in phonics among Kindergarten Level 1 (K1) ESL students using a quasi-experimental design that lasted for eight weeks. Two enrolled classes were divided into traditional (14 participants) and multimedia groups (13 participants) according to their assigned classes. The study conducted a pre-test and post-test, comparing the two groups. The test questions were sourced from the school’s standardized assessments, ensuring validity and reliability. Data obtained were analyzed and interpreted using IBM SPSS Statistics. The findings revealed a partial enhancement in CVC reading performance and a notable increase in students' interest and enthusiasm for phonics, particularly in the participants’ positive attitudes. These improvements suggest a promising trajectory in the literacy development of young learners. Understanding which instructional method best supports foundational reading skills can provide valuable insights for educators and curriculum developers. This study is among the first to focus on early education, addressing a gap in research that predominantly targets older students. Nonetheless, it is essential to note that this study is limited to the K1 students enrolled in the research.